ANALISIS KINERJA REKSA DANA SAHAM DAN REKSA DANA INDEKS LQ-45 DALAM PENILAIAN TINGKAT EFISIENSI PASAR MODAL PADA PERUSAHAAN YANG TERDAFTAR DI BEI - Nurlatifah (2013)
This research was conducted to measure the performance of equity funds and mutual funds LQ-45 index in the assessment of the efficiency of capital markets at companies listed on the stock exchanges of Indonesia from 2011. Data obtained from an equity fund as many as 43 companies and 1 funds the LQ-45 index. The analysis technique used is the raw performance and riskadjusted performance and test hypotheses using simple regression with the significant level of 5%. These results indicate that the performance of an equity fund with mutual fund performance LQ-45 index in raw performance and riskadjusted performance, and the results were positive alpha sinifikan rate of 5% on individual stocks and mutual funds in mutual funds LQ-45 index has alphanegative, the Indonesian capital market is inefficient.